1991
DOI: 10.1116/1.585769
|View full text |Cite
|
Sign up to set email alerts
|

I ns i t u doping of Si and Si1−xGex in ultrahigh vacuum chemical vapor deposition

Abstract: We report on the growth of germanium–silicon and silicon epitaxial layers by ultrahigh vacuum/chemical vapor deposition. When an in situ clean is used, films grown at 600 °C are defect-free by planar section transmission electron microscopy and no oxygen is detectable by secondary ion mass spectroscopy at the growth interface. In situ doping has been studied using B2H6/H2 and PH3/H2 as source gases. Ge0.13Si0.87 films doped with boron up to 5×1019 cm−3 have been grown and sharp doping transitions have been obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…Besides, our higher concentration P doping did not induce the lower growth rate of Si emitter. This is different from the report that Si growth rate decrease with increasing PH 3 flow [11,12]. The reason is that we set the growing temperature to 630 1C for growth the n-Si emitter layer.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…Besides, our higher concentration P doping did not induce the lower growth rate of Si emitter. This is different from the report that Si growth rate decrease with increasing PH 3 flow [11,12]. The reason is that we set the growing temperature to 630 1C for growth the n-Si emitter layer.…”
Section: Resultscontrasting
confidence: 52%
“…It will influence the doping of subsequent growth film. Besides, at lower temperature, H de-absorbing from the growth surface mainly affect film growth, this lead to lower P doping concentration and lower growth speed of Si emitter layer [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…As usual, phosphine (PH 3 ) is used as the doping gas in the UHVCVD process. 15,16 However, it was well known that the growth rate of Si will be depressed greatly with the introduction of a large amount of PH 3 . There are very few reports dealing with n-type doped Si/Si 1Ϫx Ge x epilayers grown by UHVCVD using Si 2 H 6 , GeH 4 , and PH 3 .…”
mentioning
confidence: 98%
“…Other groups have reported reduced Si thin film growth rates with increased phosphine injection. [5][6][7][8] This reduction results from the adsorption of phosphorus atoms on the Si surface which, in turn, significantly reduces the dissociative chemisorption of Si 2 H 4 . 11 Two features are apparent in the data of Fig.…”
mentioning
confidence: 99%
“…3 Ultrahigh vacuum chemical vapor deposition ͑UHV-CVD͒ studies have reported higher levels of incorporation, but with associated changes in surface chemistry and reduced growth rates. [4][5][6][7][8] Also, very high levels of n doping (Ͼ5ϫ10 19 cm Ϫ3 ) are presently achieved in the semiconductor industry using ion implantation followed by a high temperature anneal. Alternative techniques need development as device sizes shrink and low thermal budgets for processing become essential.…”
mentioning
confidence: 99%